The Unexpected Global Financial Crisis Researching Its Root Cause - Lin, Justin Yifu (The World Bank, 2012)
The world is currently still struggling with the aftermath of the worst economic crisis since the Great Depression. Following a description of the eruption, evolution and consequences of the global crisis, this paper reviews alternative hypotheses for the causes of the global financial crisis as well as their empirical evidence. The paper refutes the frequently voiced view that the global crisis was caused by global imbalances that reflected economic policies of East Asian countries. Instead, it argues that global imbalances were the result of excess demand in the United States, resulting from both the public debt in the United States arising from the Afghanistan and Iraqi wars and tax cuts and the overconsumption by households supported by the wealth effect from the housing bubble in the United States. The housing bubble itself was the outcome of the Federal Reserve's low interest rate policy in the aftermath of the burst of the "dot-com" bubble in 2001, the lack of appropriate financial regulation, and housing policies aimed at expanding the mortgage market to low-income borrowers. It was possible to maintain the large trade deficits of the United States for such a long period of time because of the dollar's reserve currency status. When the housing bubble in the United States burst, the global crisis ensued. The paper also analyzes why China's trade surplus increased significantly in general and with the United States in particular in recent years, and argues that this increase was caused by both the relocation of the labor-intensive tradable sector of East Asian economies to China and high corporate saving rates in China as a result of its dual-track approach to reform